Global Ductility Demands of RC Frames with Various Post-Yield Stiffness Ratio and Ductility Capacity Ratio Under Near-Field Earthquakes - Ade Faisal, Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The directivity pulse motion in near-field earthquake affects the responses of structures. The response includes the roof drifts and interstory drifts, which is so-called the ductility demand. Although many studies have done in this topic, the effect of various post-yield stiffness ratio and ductility capacity ratio to the global ductility demands of reinforced concrete (RC) frames under near-field ground motion is not specifically investigated yet. The trend of global ductility demands of RC frames under near-field earthquake is the objective of this study. The frames are modeled with various fundamental period, behavior factor, plastic rotation capacity, post-yield stiffness ratio, and ductility capacity ratio. The study reveals that the effect of ductility capacity ratio on the global ductility demands is apparent as as the plastic rotation capacity changes. The global ductility demand is also found influenced by global post-yield stiffness ratio and behaviour factor.